2005
DOI: 10.1038/sj.gene.6364242
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of arthritis using a QTL chip reveals a complex gene regulation of the Cia5 region in mice

Abstract: One of the major quantitative trait loci (QTLs) associated with arthritis in crosses between B10.RIII and RIIIS/J mice is the Cia5 on chromosome 3. Early in the congenic mapping process it was clear that the locus was complex, consisting of several subloci with small effects. Therefore, we developed two novel strategies to dissect a QTL: the partial advanced intercross (PAI) strategy, with which we recently found the Cia5 region to consist of three loci, Cia5, Cia21 and Cia22, and now we introduce the QTL-chip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Ity2 and Ity3 are two QTL implicated in survival to systemic Salmonella Typhimurium infection that have been identified in the wild-derived inbred mouse MOLF/ Ei (Sebastiani et al 1998).We have used congenic mouse strains in combination with expression profiling to prioritize candidate genes for each QTL, an approach that has been used successfully in finding disease-causing genes in QTL mapping studies by other groups (Rozzo et al 2001;Gu et al 2002;Mcbride et al 2003;Klein et al 2004;Johannesson et al 2005;De Buhr et al 2006). A weakness of the expression profiling approach to keep in mind, however, is that the causative effect underlying quantitative traits, such as survival to Salmonella Typhimurium infection, may not be due to differential gene expression and this approach may be associated with the potential risk of not identifying the disease gene(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ity2 and Ity3 are two QTL implicated in survival to systemic Salmonella Typhimurium infection that have been identified in the wild-derived inbred mouse MOLF/ Ei (Sebastiani et al 1998).We have used congenic mouse strains in combination with expression profiling to prioritize candidate genes for each QTL, an approach that has been used successfully in finding disease-causing genes in QTL mapping studies by other groups (Rozzo et al 2001;Gu et al 2002;Mcbride et al 2003;Klein et al 2004;Johannesson et al 2005;De Buhr et al 2006). A weakness of the expression profiling approach to keep in mind, however, is that the causative effect underlying quantitative traits, such as survival to Salmonella Typhimurium infection, may not be due to differential gene expression and this approach may be associated with the potential risk of not identifying the disease gene(s).…”
Section: Discussionmentioning
confidence: 99%
“…This congenic approach has proven fruitful in the genetic dissection of diseases such as seizure susceptibility (Ferraro et al 2004), systemic lupus erythematosus (Haywood et al 2004;Subramanian et al 2005), and type 1 diabetes (Lyons et al 2000). A combination of this classical approach to fine mapping with genomewide expression profiling techniques has been used successfully to prioritize candidate genes (Rozzo et al 2001;Gu et al 2002;Mcbride et al 2003;Klein et al 2004;Johannesson et al 2005;De Buhr et al 2006). In this article, we refine the map of the large Ity2 and Ity3 intervals and identify candidate genes combining two genetic dissection tools, the use of congenic strain mapping and expression profiling (genomewide and QTL interval-specific oligonucleotide arrays).…”
mentioning
confidence: 99%
“…More compelling are studies in model organisms where there is both biological and statistical evidence for epistasis. Three arthritis loci have been identified in a quantitative trait locus (QTL) in mice that exhibit epistatic interactions (Johannesson et al , 2005a;Johannesson et al , 2005b). Epistatic effects have also been documented in a number of other phenotypes in mice including obesity (Warden et al , 2004) and fluctuating asymmetry of tooth size and shape (Leamy et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, evidence was reported for the existence of three QTLs in the Cia5 region. 23 At this time, results do not allow us to conclude that the QTL detected in the present experiment results from the effect of a single gene or the combined effect of multiple genes, as it seems to occur at the Cia5 region, where it has been recently reported that a cluster of genes are differentially expressed during CIA 24 and it will be interesting to investigate if the same occurs in the PIA model. Interestingly, the syntenic region of this QTL in the rat has not been associated with susceptibility to PIA, 25,26 probably reflecting the different induction protocols and disease mechanisms in the two models.…”
Section: Discussionmentioning
confidence: 45%